Design of Thermoelectric Peltier Effect Demonstrator using Modul TEC-12706 and TEG-SP1848 - Pratama, Fachrizal Rian; Saraswati, Vierta (Physics Education Research Journal, 2023)
Thermoelectric devices have several advantages, including no moving parts, noise-free operation, long service life, zero-emission, and precise temperature control. Therefore, they have been widely used in solid-state cooling, heating, and power generation. The study of the Thermoelectric Peltier Effect Demonstrator can provide insights into the potential applications and benefits of thermoelectric devices. This research aims to investigate the Thermoelectric Peltier Effect Demonstrator and its applications in solid-state cooling and heating. Specifically, the study aims to examine the Peltier effect generated by applying an electric current to the TEC-12706 and TEG-SP1848 modules connected to a heatsink and placed in a container filled with water. The research methodology involves conducting experiments using the Thermoelectric Peltier Effect Demonstrator. The modules are connected to the heatsink and placed in a water-filled container, and an electric current is applied to generate the Peltier effect. The temperature changes on both sides of the modules and the amount of heat transfer are measured and recorded. The results of the experiments show that the Thermoelectric Peltier Effect Demonstrator can effectively generate the Peltier effect and produce temperature differences between the two sides of the modules. The amount of heat transfer can also be controlled by adjusting the electric current. These findings demonstrate the potential applications of thermoelectric devices in solid-state cooling and heating, as well as their ability to provide more precise temperature control compared to conventional compressors.